1989
DOI: 10.1007/bf00290833
|View full text |Cite
|
Sign up to set email alerts
|

RFLP-based genetic maps of wheat homoeologous group 7 chromosomes

Abstract: Restriction fragment length polymorphism (RFLP) mapping was attempted using 18 cDNA clones, 14 anonymous and 4 of known function, which had been shown to have homologous DNA sequences on the group 7 chromosomes of wheat. The loci identified by these probes have been mapped on one or more chromosomes in this homoeologous group using linkage data derived from various F2, random inbred, doubled haploid and single chromosome recombinant populations. The maps also include three isozyme loci, five disease resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
207
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 515 publications
(221 citation statements)
references
References 31 publications
10
207
0
4
Order By: Relevance
“…linkage maps show clustering of markers near the centromere. This has been observed in other studies of wheat (Dvorak and Chen 1984;Snape et al 1985;Dvofiik and Appels 1986;Curtis and Lukaszewski 1991;Chao et al 1989;Devos et al 1992Devos et al , 1993bWerner et al 1992;Lukaszewski and Curtis 1993), barley (Kleinhofs et al 1993), rye (Rogowsky et al 1992;Lukaszewski 1992), and oat (O'Donoughue et al 1992). Comparisons of the physical (Fig.…”
Section: Recombinationsupporting
confidence: 78%
See 3 more Smart Citations
“…linkage maps show clustering of markers near the centromere. This has been observed in other studies of wheat (Dvorak and Chen 1984;Snape et al 1985;Dvofiik and Appels 1986;Curtis and Lukaszewski 1991;Chao et al 1989;Devos et al 1992Devos et al , 1993bWerner et al 1992;Lukaszewski and Curtis 1993), barley (Kleinhofs et al 1993), rye (Rogowsky et al 1992;Lukaszewski 1992), and oat (O'Donoughue et al 1992). Comparisons of the physical (Fig.…”
Section: Recombinationsupporting
confidence: 78%
“…The highest degree of polymorphism was detected in chromosome 1B and the lowest in ID, in spite of the fact that one parent in the 7: aestivum cross contains 1D from 7: tauschii, the D genome progenitor of T. aestivum (McFadden and Sears 1946). Chao et al (1989) also reported the lowest level of polymorphism in the D genome of chromosome 7 of 7: aestivum. High levels of polymorphism have been reported among T. tauschii accessions (Gill et al 1991), but by chance, the accession used to produce the T. aestivum synthetic line used in this study is genetically similar to the latter's progenitor.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Mapas genéticos que levaram décadas para serem desenvolvidos em virtude da restrita disponibilidade de marcadores morfológicos e isoenzimáticos foram amplamente saturados com o uso de marcas moleculares. Assim ocorreu em milho (HELENTJARIS et al, 1986), arroz (MCCOUCH et al, 1988), trigo (CHAO et al, 1989), batata (GEBHARDT et al, 1989) e tomate (TANKSLEY et al, 1992). Várias espécies para as quais os estudos de herança são restritos, e tampouco foi descrita ligação gênica entre qualquer tipo de marcador, tiveram mapas genéticos rapidamente desenvolvidos, como o eucalipto (GRATTAPAGLIA e SEDEROFF, 1994), kiwi (TESTOLIN et al, 2001) e maracujá (CARNEIRO et al, 2002).…”
Section: Introductionunclassified